2012
DOI: 10.1182/blood-2011-09-378117
|View full text |Cite
|
Sign up to set email alerts
|

PU.1 is linking the glycolytic enzyme HK3 in neutrophil differentiation and survival of APL cells

Abstract: The transcription factor PU.1 is a master regulator of myeloid differentiation and function. On the other hand, only scarce information is available on PU.1-regulated genes involved in cell survival. We now identified the glycolytic enzyme hexokinase 3 (HK3), a gene with cytoprotective functions, as transcriptional target of PU.1. Interestingly, HK3 expression is highly associated with the myeloid lineage and was significantly decreased in acute myeloid leukemia patients compared with normal granulocytes. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 38 publications
4
74
0
Order By: Relevance
“…p62/SQSTM1 mRNA levels were quantified by RT-qPCR in primary CD34 þ progenitor cells, in granulocytes from healthy donors and in AML subtypes FAB M0-M4 harboring the following molecular lesions: (inv(16), t(8;21), t(15;17)) K ¼ Karyotype Federzoni et al 53 Ct values were normalized to HMBS and ABL1 ( À DCt) and represent log 2 expression levels. Mann-Whitney U-test *Po0.05; **Po0.01; ***Po0.001 p62/SQSTM1 role during granulocytic differentiation A Trocoli et al mechanism during granulocyte differentiation of AML cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p62/SQSTM1 mRNA levels were quantified by RT-qPCR in primary CD34 þ progenitor cells, in granulocytes from healthy donors and in AML subtypes FAB M0-M4 harboring the following molecular lesions: (inv(16), t(8;21), t(15;17)) K ¼ Karyotype Federzoni et al 53 Ct values were normalized to HMBS and ABL1 ( À DCt) and represent log 2 expression levels. Mann-Whitney U-test *Po0.05; **Po0.01; ***Po0.001 p62/SQSTM1 role during granulocytic differentiation A Trocoli et al mechanism during granulocyte differentiation of AML cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were grown in a humidified incubator at 37 1C with 5% CO 2 and 95% air. 53 Isolation of primary cells and in vitro differentiation of CD34 þ progenitor cells was done as described earlier. 54 The details of patients examined in the study are indicated in Supplementary Table. Immunofluorescence study.…”
Section: Discussionmentioning
confidence: 99%
“…Confocal microscopic analysis confirmed that membrane-associated GLUT1 was similar between HD and GSD-Ib neutrophils ( Figure 2E). The expression of HK1 mRNA is downregulated and HK2 is unchanged, but the expression of HK3, the major HK isozyme in neutrophils, 35,36 BLOOD, 1 MAY 2014 x VOLUME 123, NUMBER 18 …”
Section: Resultsmentioning
confidence: 99%
“…Glucose uptake can also be controlled by glucose phosphorylation. The major HK isozyme in neutrophils is HK3, 36 which also plays the role of protecting cells from oxidant-induced cell death. 46 The expression of HK3 is upregulated by HIF-1a, 46 and consistent with this we observed that both HK3 mRNA and protein are increased 4-fold in G6PT-deficient neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, myeloid cells express high levels of the transcription factor PU.1, which transactivates HK3 to drive myeloid differentiation and maintain myeloid identity (Federzoni et al, 2012). Myeloid progenitors also express lower levels of PDKs, suggesting that PDK-mediated suppression of OxPhos in HSCs is relieved upon myeloid commitment (Klimmeck et al, 2012;Takubo et al, 2013).…”
Section: Hematopoietic Progenitorsmentioning
confidence: 99%